A Geophysical Characteristic Over Kelud Caldera Post November 2007 Eruption - Imam, Suyanto (Pusat Studi Panas Bumi Fakultas Teknik UGM, 2010)
VLF and a ground magnetic survey were carried out over the Kelud Caldera, East Java in January 2009. The new lava dome emerged in the November 2007 eruption and filled the western part of the previous caldera. The survey lines are located at the eastern part of this new dome. Preliminary